Is Punica granatum Efficient Against Sepsis? A Comparative Study of Amifostine Versus Pomegranate - Kazim Sahin; Sena Sahin Aktura; Ilkay Bahceci; Tolga Mercantepe; Levent Tumkaya; Atilla Topcu; Filiz Mercantepe; Omer Faruk Duran; Huseyin Avni Uydu; Zihni Acar Yazici (Life)
Sepsis is a clinical condition causing tissue damage as a result of infection and an exaggerated immune response. Sepsis causes 11 million deaths annually, a third of which are associated with acute lung injury (ALI). Rapid and effective treatment is crucial to improve survival rates. Punica granatum (pomegranate) is rich in polyphenols and demonstrates strong antioxidant activity, while amifostine acts as a free radical scavenger. This study aimed to investigate the antioxidant and anti-inflammatory effects of P. granatum peel extract (PGPE) and amifostine in sepsis-related ALI. Experimental groups included Control, CLP (cecal ligation and puncture-induced sepsis), Amf (200 mg/kg amifostine, intraperitoneally), and PGPE250, and PGPE500 (250 and 500 mg/kg PGPE via oral gavage, respectively). Thiobarbituric acid reactive substances (TBARS), total thiol (TT), tumor necrosis factor-alpha (TNF-α) levels, and metalloproteinases 2 and 9 (MMP-2 and MMP-9) were assessed in the lung tissue. Biochemical analysis demonstrated that TBARS and TNF-α levels significantly decreased in both the PGPE and amifostine treatment groups compared to the CLP group, while TT levels showed notable improvement. Histopathological evaluation revealed reduced MMP-2 and MMP-9 immunopositivity in the PGPE250 and PGPE500 groups. These findings highlight the lung-protective properties of PGPE, underscoring its potential as a therapeutic agent for sepsis-induced acute lung injury.